Notes on fiber length measurements: A case study in the underbelly of open source neuroscience - Claude J Bajada; Robert E Smith; Svenja Caspers (NeuroImage, 2022)
Being on the bleeding edge of research requires the use of new and regularly updated software. The result is the occasional and inevitable occurrence of bugs. In the following work we present a case study where a feature request introduced a bug in a neuroimaging software package, which had consequences for the quality of results in a published article. We discuss the process of diagnosis, rectification and analysis replication.